Bilingual education for the deaf - Silva, Izilda de Carvalho Noleto (2021)
The present article aims to reflect on the quality of education for deaf children in our country. First, we will raise some theories that prove to us how the use of Brazilian Sign Language is essential for the teaching and learning process of deaf students. After this, we will present, briefly, how some historical verifications show us that deaf individuals need to master the processes of reading and writing of portuguese language in order to fully exercise their rights as citizens. Once this is understood, we move on to propose the majestic bilingual education for the deaf. We conclude with a synthesis of the main theories discussed and with a reflection on how important it is for teachers to become bilingual so that they can use the Brazilian Sign Language to significantly teach their students to master the processes of reading and writing and thus prepare them to exercise their citizenship.